A new species and a new record of Perlodidae (Plecoptera) from China - Chen, Zhi-Teng (Zootaxa, 2019)
A new species of Filchneria Klapálek 1908, F. songi sp. nov. from Shaanxi Province of northwestern China is described and illustrated based on male, female, and eggs. Morphological comparisons are provided with related taxa. Skwala compacta (McLachlan, 1872) is newly recorded from Xinjiang Uygur Autonomous Region of northwestern China. New illustrations are provided for Chinese specimens of S. compacta.